2019
DOI: 10.1029/2018tc005296
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Controls on Taupo Volcanic Zone Geothermal Expression: Insights From Te Mihi, Wairakei Geothermal Field

Abstract: Information on structure, stress, and their interrelationship is essential for understanding structurally controlled geothermal permeability. Active fault mapping, borehole image analysis, and well testing in the Te Mihi geothermal area, New Zealand, allows us to refine structural and fluid flow architecture of this resource. The Te Mihi area is structurally complex, comprising a set of NW dipping master faults containing pervasive SE dipping antithetic and splay structures in their hanging walls. These faults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 81 publications
(126 reference statements)
3
37
0
Order By: Relevance
“…The GVR image logs were statically and dynamically normalized to enhance resistivity contrasts for improved feature identification, with a 1 and 0.5 m normalization window used for the latter. Feature classification is based on criteria set out in McNamara et al (2019). Quality rankings and circular statistics for stress induced borehole features identified from the GVR image logs follow World Stress Map criteria (Heidbach, 2016).…”
Section: Gvr Resistivity Image Log Processing and Analysismentioning
confidence: 99%
“…The GVR image logs were statically and dynamically normalized to enhance resistivity contrasts for improved feature identification, with a 1 and 0.5 m normalization window used for the latter. Feature classification is based on criteria set out in McNamara et al (2019). Quality rankings and circular statistics for stress induced borehole features identified from the GVR image logs follow World Stress Map criteria (Heidbach, 2016).…”
Section: Gvr Resistivity Image Log Processing and Analysismentioning
confidence: 99%
“…Johri et al (2014) did interpret damage zones around faults from image logs; they encountered damage zones of 50 to 80 m in total. McNamara et al (2019) found high fracture density zones both within and outside projected fault zones in four boreholes, in volcanic lithologies. A spatial correlation between fault zones and larger fracture densities was only found in one of the boreholes.…”
Section: Fracture Frequency Near Possible Faultsmentioning
confidence: 83%
“…Since FMI and acoustic image logs result in an oriented image of the borehole wall, they provide valuable in situ information on the reservoir characteristics and are widely used to characterise geothermal reservoirs. Image logs have been studied to identify sedimentological and structural features in the subsurface, such as bedding planes, fractures and faults, and to obtain information on in situ stress orientations (Tenzer et al, 1991;Dezayes et al, 1995;Genter et al, 1997;Prensky, 1999;Trice, 1999;Poppelreiter et al, 2010;Massiot et al, 2015;Williams et al, 2016;McNamara et al, 2019). Fractures and bed boundaries and their characteristics were quantified from the FMI log of the MOL-GT-01 borehole.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Landsat image has been implemented in a various applications, e.g. in the ecology ( Salas et al., 2017 ), Environmental ( Wang and Li, 2017 ), in water resources ( Abdelaziz et al., 2008 ; Abdelaziz and Bakr, 2012 ; Abdelaziz and Merkel, 2012 ; Edet et al., 2014 ; Abdelaziz and Le, 2014 ; Abdelaziz and Bambi, 2016 ) geothermal resources ( Qin et al., 2011 ; McNamara et al., 2016 ), mineral exploration ( Mia and Fujimitsu, 2012 ), and Agriculture ( Prishchepov et al., 2012 ). Many researchers around the world have used remote sensing data to differentiate serpentinized ultramafic rocks, which are hold potential for many types of deposits (e.g.…”
Section: Discussionmentioning
confidence: 99%